The Relationship Between Blood Pressure Increase and Sleep Quality of Hypertension Sufferer in Lebaksitu Village - Friska, Friska; Rohman, Abdul; Hasanah, Nurul Azizah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: to determine the relationship between increased blood pressure and changes in sleep quality in hypertension sufferers. Method: The study design used a correlational approach with a cross-sectional method. The number of samples was 66 respondents using a purposive sampling technique. Data collection techniques used a sleep quality questionnaire and standardized manual blood pressure measuring instrument. Data processing included editing, coding, entry and cleaning with the SPSS application to analyze univariate and bivariate. Results: this study showed that the majority of blood pressure in hypertension sufferers was in the grade I category of 45.6% with poor sleep quality of 81.8%. The results of this study also showed a significant relationship between increased blood pressure and sleep quality in hypertension sufferers with a significance value of 0.028 (<0.05). Conclusion: Increased blood pressure causes headache symptoms in hypertension sufferers which disrupts the sleep cycle and worsens the quality of sleep in hypertension sufferers.